Mode of Action of the Antibiotic Siccanin on Intact Cells and Mitochondria of Trichophyton mentagrophytes - Nose, Keinosuke (1971)
Siccanin at 3 μg/ml completely inhibited the growth of Trichophyton mentagrophytes. The primary site of action of siccanin on T. mentagrophytes is succinate dehydrogenase in the terminal electron transport system. At a concentration of siccanin giving 50% inhibition of growth (0.3 μg/ml), respiration of intact cells was inhibited more strongly than any other cellular functions tested, including the syntheses of cellular ribonucleic acid, deoxyribonucleic acid, phospholipid, protein, and cell wall fractions. In addition, at the same concentration siccanin did not cause any detectable damage in the permeability of the cells. Furthermore, the oxidation of succinate in mitochondrial preparation is more sensitive to the antibiotic than respiration in intact cells. Oxidation of other substrates tested was less sensitive to siccanin than that of succinate. The antibiotic inhibited both phosphorylation and oxidation, without causing changes in the P:O ratio. Siccanin at 0.03 μg/ml, which caused 50% inhibition of succinate oxidation in mitochondria, had effect neither on the exchange reaction between inorganic phosphate (P(i)) and adenosine triphosphate (ATP) nor on that between adenosine diphosphate and ATP. An ATP phosphohydrolase activity was also insensitive to the antibiotic. At very high concentrations, however, the antibiotic slightly inhibited the P(i)-ATP exchange reaction. From those results, it was concluded that siccanin inhibits fungal growth by inhibiting the respiratory electron transport system.